2012
DOI: 10.1002/pssb.201248412
|View full text |Cite
|
Sign up to set email alerts
|

Lattice dynamics and structure of GeTe, SnTe and PbTe

Abstract: The lattice dynamics in the IV-VI compounds GeTe, SnTe and PbTe were studied by 125 Te and 119 Sn nuclear inelastic scattering and the obtained partial density of phonon states were compared with published theoretical calculations. The phase purity and structure were characterized by high energy X-ray diffraction. The effect of the atomic arrangement, rhombo-hedral for GeTe and cubic for SnTe and PbTe, is visible in the density of phonon states. Vibrational properties are found to be in good agreement with ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
105
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(133 citation statements)
references
References 63 publications
14
105
0
3
Order By: Relevance
“…The larger cation MSD was noted in Ref. 59 , but no clear origin for the effect was found. Our detailed DFT simulations actually reveal that these large MSD values for cations arise from the weaker on-site force-constants for cations, in good agreement with prior DFT investigations of the bonding and phonons in these materials [13][14][15][16]38 .…”
Section: Atomic Distributionsmentioning
confidence: 74%
See 2 more Smart Citations
“…The larger cation MSD was noted in Ref. 59 , but no clear origin for the effect was found. Our detailed DFT simulations actually reveal that these large MSD values for cations arise from the weaker on-site force-constants for cations, in good agreement with prior DFT investigations of the bonding and phonons in these materials [13][14][15][16]38 .…”
Section: Atomic Distributionsmentioning
confidence: 74%
“…29 The partial phonon densities of states (DOS) of Sn and Te were previously measured in rock-salt SnTe at 60 K using nuclear-resonant inelastic x-ray scattering, and it was found that the phonons are softer than similar materials in rhombohedral phase. 59 In addition, lattice dynamics study of SnTe using Mössbauer spectroscopy suggested the existence of low-temperature anharmonicity. 60 Our more detailed measurements of the temperaturedependent phonon dispersions and DOS provide further information about the phonon dynamics and anharmonicity, and also enable to clarify the origin of asymmetric PDF/RDF peaks observed in diffraction experiments.…”
Section: Lattice Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2A shows the orthorhombic crystal structure for compounds such as SnSe, SnS, GeSe, and GeS in the Pnma-phase (#62) (Tritsaris et al, 2013;Ding et al, 2015;Guo et al, 2015;Wang et al, 2015), and Figure 2B shows the hexagonal crystal structure for compounds such as SnSe2 and SnS2 in the P3m1-phase (#164) (Sava et al, 2006;Bauer Pereira et al, 2013;Sun et al, 2015). For each simulation, only one layer was considered, where the number of atoms per primitive cell is 4 for the orthorhombic crystal structure and 3 for the hexagonal crystal structure.…”
Section: Computational Detailsmentioning
confidence: 99%
“…15 Since the experiments are performed in the transmission geometry, the observed dynamics is determined by the averaged contribution along the direction …”
Section: Transient Change Of Diffraction Intensity and Peak Positionmentioning
confidence: 99%